Self-diagnosing braided composite rod - Fangueiro, Raúl (2010)
This paper presents the development of a braided reinforced composite rod (BCR) able to both reinforce and monitor the stress state of concrete structures. Carbon fibers have been used as sensing and reinforcing materials along with glass fiber. Various composites rods have been produced using an author patented technique based on a modified conventional braiding machine. The materials investigated were prepared with different carbon fiber content as follows: BCR2 (77% glass/23% carbon fiber), BCR3 (53% glass/47% carbon fiber), BCR4 (100% carbon fiber). BCRs have been tested under bending while the variation of the electrical resistance was simultaneously monitored. The correlations obtained between deformation and electrical resistance show the suitability of the rods to be used as sensors. The fractional resistance change versus strain plots show that the gage factor increases with decreasing carbon fiber content.